The effect of composition and substrate fermentation duration on microbial fuel cell electrical energy - Christin Vera Natalia Ginting; Jumaida Sari Nasution; Malik Alfatah Sembiring; Murniaty Simorangkir (Pascasarjana Universitas Negeri Medan, 2019)
Organic vegetable wastes such as mustard vegetables found in traditional markets, especially Medan, are quite abundant and the increase in electricity demand is not matched by the availability of adequate energy sources, encouraging efforts to find alternative sources of renewable energy, economical and environmentally friendly. Microbial Fuel Cell (MFC) reactors can be used as an alternative energy source that converts chemical energy into electrical energy through biocatalytic reactions using microorganisms by utilizing organic materials. This study aims to determine the effect of the use of mustard vegetable waste substrate with a variety of starters and fermentation duration in the MFC reactor system to the voltage and current of electrical energy generated. The design of this study used a factorial 4x2 Completely Randomized Design consisting of two factors, namely factor A substrate composition and fermentation duration B factor. The results showed that there was an influence of substrate composition and fermentation duration on the MFC reactor system on the electrical energy generated by the system. Electricity (I) (20.1 mA) and voltage (72.13 mV) highest electricity produced by MFC reactor with composition of glucose substrate and EM4 starter with 5 days fermentation duration, followed by the treatment of vegetable mustard waste and EM4 with a fermentation duration of 5 days (15.2 mA and 68.76 mV). In terms of economics, the use of vegetable mustard waste substrate material with EM4 starter in the MFC reactor has more potential to be developed than using glucose substrates which are relatively more expensive.Keywords: Electric energy; fermentation duration; microbial fuel cell; mustard vegetable waste